PENERAPAN METODE TOPSIS DALAM SISTEM PENERIMAAN SISWA BARU DI SMK NUSANTARA - Tombilayuk, Lapu (Fakultas Teknik, Universitas Tadulako, 2021)
The new student admission system carried out at the Nusantara Bontang Vocational High School is one of the academic processes that is routinely carried out every year. At this time the data processing process for selecting prospective new students for the program is still done manually, where registration is done directly by coming to the school by filling out the registration form and the student admissions committee does the selection manually. The value processing process takes a long time, especially in the selection process and ranking process. A decision support system is the right system to apply because a decision support system can help make decisions based on criteria. The method used in this research is the TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution). The TOPSIS method is used because it is based on the concept that the best alternative not only has the shortest distance from the positive ideal solution but also has the longest distance from the negative ideal solution, resulting in an accuracy rate of 90% from the application of the TOPSIS method in the new student admission system at SMK Nusantara.